PENETAPAN KADAR FLAVONOID TOTAL DAN UJI TOKSISITAS AKUT EKSTRAK DAUN AFRIKA (Vernonia amygdalina Del.) PADA MENCIT JANTAN DDY - Christine Meidiawati; Ummu Mastna Zuhri; Sesilia Andriani Keban; Wiwi Winarti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
One of the plants that is efficacious as an antifertilitas that grows is Vernonia amygdalina Del. This plant empirically has been to treat various diseases, but have no scientific data. Aims of this research is to obtain a ethanol 70% extract of leaves of Vernonia amygdalina Del. which safely for use to test animals mice DDY. Phytochemical screening carried out based on the literature from Farnsworth and the Ministry of Health of the Republic of Indonesia (2000). Determination of total flavonoid using the colorimetric method of aluminum chloride and total alkaloid with complex methods bromocresol green. Safety testing I which is conducted is acute toxicity test (LD₅₀) by the method of Weil C.S. The results showed that the Africa leaf extract contains alkaloids, flavonoids, saponins, tannins, quinones, and steroids/triterpenoids. It was found that the levels of total flavonoids was 1.27%, while for safety testing I are found that the 70% ethanol extract of Africa leaves has a LD50 greater than 16 g / kg that are categorized practically non-toxic.